Konsep Rukhsah bagi Tenaga Medis dengan Alat Pelindung Diri saat Menangani Pasien COVID-19 - Camelia Rizka Maulida Amel (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2020)
Many scholars have discussed the principle of freedom on Islamic law, Particularly the topic related to qawa'id fiqhiyyah and one of which is the principle of al-mashaqqah tajlibu al-taysir (Difficulty calls for facilitation). This research is a qualitative study in which the method used is a descriptive and qualitative one to analyze or describe facts or problems that arise in the medical team with personal protective equipment (APD) relating to MUI fatwa number 17 of 2020 through direct or indirect approach and its relevance to the concept of rukhsah in the rules of al-mashaqqah tajlib al-taysir (Difficulty calls for facilitation). This article concludes that a rukhsah relating to the principle of al-mashaqqah tajlib al-taysir which give rise to the difficulty relating to the massive spread of Covid-19 is not because of negligence but the use of APD while it is not possible to perform wudu' or use dust (tayammum), so the medical team falls under the category of faqid al-tahurain. Thus, the medical personnel who wears APD are permissible to perform prayer without performing wudhu' or tayammum.